FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KETUBAN PECAH DINI PADA IBU BERSALIN DI PUSKESMAS TANGGEUNG CIANJUR - Andi Julia Rifiana (Jurnal Ilmu dan Budaya, 2018)
Premature rupture of membranes is defined as prematurely ruptured membranes of the membranaes. This incidence of premature rupture of membranes occurs 10% in all pregnancies. Incidence of premature rupture of membranes in Tanggeung health center 33 case KPD. This studi aims to determine factores related to premature rupture of membranes in maternal mothers at Tanggeung Health Center Cianjur District year 2017 using a cases control approach. Population in this research is mother of birth, while the sample used 1 : 1 between case and control, so the number of samples of 66 maternity mothers. The data collected in this study is using secondary data from medical records Tanggeung Health Center. The results of this study were conducted with univariate and bivariate techniques by using Chi Square test. Primipara gravida research results as many 42 people (63,6%), ge is at risk <20 year ≥ 35 year as many 44 people (66,7%), anemia as many 39 people (59,1%) and not gemeli as many 63 people (95,5%) Conclusion there is a significant relationship between gravida (ρ =0,005OR 5,400), mother`s age (ρ=0,001OR 8,700), and anemia (ρ= 0,003OR 5,714). There is no significant relationship between gemeli pregnamncy (ρ=0,492) with premature rupture of membranes at Tanggeung Health Center, Cianjur district year 2017. Suggestions for officers to di high riskscreening in pregnant women at risk and anemia to prevent premature rupture of membranes with recommending a reguler ANC and administration of added blood tablets according to degree of anemia.